2018
DOI: 10.1002/jmv.25274
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and seroprevalence of hepatitis E evaluated in frozen‐serum samples (2002‐2003) of pregnant women compared with female blood donors in a Southern region of Brazil

Abstract: Hepatitis E has always been related to morbidity in pregnant women. Its epidemiology is not well understood in Brazil. Therefore, we tested sera from 209 pregnant women and 199 female blood donors, collected at a single center in Curitiba, Brazil. The Wantai assay was used for testing the anti-hepatitis E virus (anti-HEV), immunoglobulin G (IgG), and an in-house polymerase chain reaction process for testing HEV RNA. Anti-HEV was detected in 22.5% of the total group, 19% in the pregnant women group, and 26% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…HEV is a non-enveloped virus with a positive sense single stranded RNA genome. According to its genetic variability, it has been classified into 8 genotypes [1][2][3][4][5][6][7][8], from which 5 of them can infect humans (1 to 4 and 7) [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HEV is a non-enveloped virus with a positive sense single stranded RNA genome. According to its genetic variability, it has been classified into 8 genotypes [1][2][3][4][5][6][7][8], from which 5 of them can infect humans (1 to 4 and 7) [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…In South America, there are very few studies about HEV detection in pregnant women, performed in Venezuela and Brazil in the 1990's decade, which report IgG anti-HEV seroprevalences of 1.0, 1.3 and 1.9% [6,7]. After several years, a study from Brazil reported a much higher prevalence of 19% in the pregnant women group, showing no significant differences with blood donors from the same region [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, HEV-3 is the only genotype identified (Gardinali et al, 2012a;Lopes Dos Santos et al, 2010;Vasconcelos et al, 2015), and anti-HEV IgG prevalence rates vary from 0 to 38% (Bortoliero et al, 2006;Carrilho et al, 2005;Hardtke et al, 2018;Lyra et al, 2005;Martins et al, 2014;Passos-Castilho et al, 2016;Silva et al, 2012;Trinta et al, 2001;Vitral et al, 2014) among specific populations. However, the associated risk factors are not well known.…”
Section: Introductionmentioning
confidence: 99%
“…On review of full‐text articles for the remaining 140 citations, 83 did not meet selection criteria. Of the 57 citations selected for final data synthesis , one provided three data sets ; hence, we had a total of 59 data sets from 28 countries (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…A large majority of data sets were from Europe, high or high‐middle income countries in Asia and North America (27, 12 and 4 data sets, respectively); by comparison, there were only eight studies from low/low‐middle income countries of Asia and Africa; the remaining eight data sets were from other parts of the world. In 39 data sets, all the blood units had been tested for HEV RNA, whereas in 20 data sets, the blood units were first screened for the presence of anti‐HEV antibodies ( n = 17) or for elevated serum ALT levels ( n = 3) , with only the screen‐positive units being tested for HEV RNA.…”
Section: Resultsmentioning
confidence: 99%